Federalisation and education in Nepal: contemporary reflections on working through change. Issue 2 (17th February 2020) - Daly, Angela; Parker, Sara; Sherpa, Samden; Regmi, Umesh
ABSTRACT: This paper presents reflections from recent research on the opportunities and barriers for education in Nepal in the context of federalisation. Public administration of services including education is subject to major reorganisation as a national priority. By 2019, new structures of local governance will be established, presenting an opportunity for improved coordination of education, health and social work at regional and municipality levels. Drawing on interviews with academic, school-based and NGO stakeholders, findings offer a contemporary commentary on processes, power and possibilities to improve educational inclusion and progress towards the Sustainable Development Goal 4: Quality Education.